2019
DOI: 10.1145/3359184
|View full text |Cite
|
Sign up to set email alerts
|

"I feel like only half a man"

Abstract: Judith (2019) "I feel like only half a man": Online Forums as a Resource for Finding a "New Normal" for Men Experiencing Fertility Issues. Proceedings of the ACM on Human-Computer Interaction, 3 (CSCW). p. 82.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Such an instrumental approach to menstruation prescribes "the forms of knowledge and types of relationships with their body" those who menstruate are regarded as likely to embrace [26], opposed to how these technologies could exist diferently in ways that would "encourage self-knowledge and afrm and support the needs of diferent kinds of menstruating bodies" [24]. On the other hand, some have specifcally looked into fertility from a holistic viewpoint [13] to advance collaborative and supportive approaches [15] and dealing with emotions [14], attended to fertility tracking apps (FTAs) [66], infertility in men [56], through to ovulation tracking devices that aid conception [31]. Generally, these technologies seek to support conception, and individuals can record "menstruation and bodily signs of ovulation with the promise of producing more detailed knowledge of the individual's menstrual cycle and predictions of their most fertile days or fertile window in the cycle" [29].…”
Section: Introductionmentioning
confidence: 99%
“…Such an instrumental approach to menstruation prescribes "the forms of knowledge and types of relationships with their body" those who menstruate are regarded as likely to embrace [26], opposed to how these technologies could exist diferently in ways that would "encourage self-knowledge and afrm and support the needs of diferent kinds of menstruating bodies" [24]. On the other hand, some have specifcally looked into fertility from a holistic viewpoint [13] to advance collaborative and supportive approaches [15] and dealing with emotions [14], attended to fertility tracking apps (FTAs) [66], infertility in men [56], through to ovulation tracking devices that aid conception [31]. Generally, these technologies seek to support conception, and individuals can record "menstruation and bodily signs of ovulation with the promise of producing more detailed knowledge of the individual's menstrual cycle and predictions of their most fertile days or fertile window in the cycle" [29].…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has found that online communities focused on reproductive healthcare (e.g., pregnancy, vulvodynia) employ strategies related to validation (Andalibi and Garcia 2021), information management (Patel et al 2019;Young and Miller 2019;Andalibi and Garcia 2021), personal tracking (Chopra et al 2021), and identifying causation (Patel et al 2019). We find these themes again in our birth control communities, with variations; for example, personal tracking is also a prominent theme in birth control discussions, but it is focused on pill timings and calculations and on selfobservations of side effects.…”
Section: Discussionmentioning
confidence: 65%
“…In online healthcare communities, the individual works to make sense of their healthcare experience, and the community collectively gathers information, compares stories, and makes sense of a shared experience (Mamykina, Nakikj, and Elhadad 2015). Sharing experiences can help narrators make sense of their stories (Tangherlini 2000) and can transfer important information to others without firsthand experience (Bietti, Tilston, and Bangerter 2019), leading users through a transformative process via the gathering and organizing of information (Genuis and Bronstein 2017;Patel et al 2019). This process is contextual; each community can rely on different strategies (Young and Miller 2019).…”
Section: Related Workmentioning
confidence: 99%
“…While girls grow up amid sociocultural constructs of eventual motherhood as defining femininity, fatherhood is not built as a necessity for men (Letherby, 1999(Letherby, , 2002Russo, 1976). We do not suggest that IC is an issue that is only relevant to women or that men go unaffected, and previous research does show that men communicate online about fertility issues (Malik & Coulson, 2008;Patel et al, 2019); however, our analysis of TTC communication on Instagram shows that an overwhelming majority of participants are female, and this study thus accounts particularly for women's experiences and vulnerabilities.…”
Section: Introductionmentioning
confidence: 56%